Unos cuadros de Isabel de Farnesio tasados por Antón Rafael Mengs para el infante don Luis - Sophie Dominguez-Fuentes (Mélanges de la Casa de Velázquez)
Upon the death of his mother on 11 June 1766, the Infante don Luis (1727-1785), youngest son of Philip V and Isabel de Farnesio, inherited one hundred and nine paintings, five sculptures and a copper plate from one of the most prestigious collections of the 18th century. A study of the late queen’s will not only tells us the contents of the prince’s inheritance but also highlights the importance of this legacy in enhancing Don Luis’s collection of paintings, which was founded in 1740 with the purchase of some paintings belonging to the late queen Mariana of Neuburg. It reveals the assistance of Antón Rafael Mengs, commissioned to appraise the works belonging to Isabel de Farnesio, indicating that the Infante sought his services once again in 1768 when he decided to buy seventy-two paintings, also from his mother’s collection. Commissioned by the Infante to select and appraise these paintings, Mengs drew up a number of lists (1768-1771) which throw light on the eclectic tastes of the enlightened prince. They also reveal the problems of succession that the artist had to face and the trends in the Spanish art market in the 18th century.